INTEGRATION OF ARCHITECTURE AND LANDSCAPE ON SLOPING SITES: A SUSTAINABLE APPROACH TO BUILDING DESIGN - Widiantara, I Wayan Andhika; Nursanty, Eko; Cauba, Arturo G (Border: Jurnal Arsitektur, 2024)
This paper investigates the adaptation of sustainable architectural designs for sloping sites by building in the natural context. While sloping sites can create certain design restrictions, they can also be a source of design innovation that takes advantage of the existing topography. The present research aims to determine design approaches, which build both visual and functional equilibrium to the buildings, while efficiently providing comfort and ecological nature of the buildings. The use of qualitative analysis of four case studies, Ncaved House in Greece, UCCA Dune Art Museum in China, La Escondida Apartments in Mexico, and Private House in Thusis in Switzerland reveals that the successful integration of buildings into the landscape is aided by the usage of local materials, use of daylight and cross-ventilation and shelter from extreme weather conditions among other factors. Each case study looks at how the design resolved the challenge of a sloped site and perspectives of ecology and aesthetics. These insights are important for designers as they address the issue of how to maximize the design’s ecological sensitivity and beauty, without shunning sloped sites but instead using them as positives in the overall architectural design scheme.